A Review: Role of Aldosterone in Hypertension - Audu, Jankada Patience; Chikata, Ezugwu Hilary; Ipav, Selumun Solomon; Umaru, Isaac John; Iseko, Kingsley Iyoko; Istifanus, Dafup Katdel (Darul Yasin Al Sys, 2024)
In Western societies, hypertension affects up to 20% of the population, making it a significant public health concern. The rates of blood pressure control remain unsatisfactory despite advancements in treatment. Since hypertension is a complex disorder, there is rarely a single, obvious cause identified for so-called